Nano carbon cage as well as preparation method and application thereof
By physical mixing, roasting and pickling the asphalt and nickel -containing compounds, the problems of complex and cost -high costs of the existing nano -carbon cage preparation methods are solved, and nano -carbon cages with high gravitarization and structural constitution are prepared. Suitable for the negative electrode of lithium ion capacitors, which improves electrochemical performance.
Patent Information
- Application Number
- CN202310916585.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-07-25
AI Technical Summary
The existing nano carbon cage preparation methods have problems such as complex production processes, high raw material costs and low carbon yield, making it difficult to achieve large-scale production, and the regularity and uniformity of the structure also need to be improved.
Use asphalt and nickel -containing compounds for physical mixing, and then bake and pickle. To prepare nano -carbon cages through this method, avoid using nanosometer, reduce the cost of raw materials, and increase the degree of graphization and structure of carbon cages. sex.
The nano -carbon cage with low preparation cost and simple process has a high gravitarization degree and structural regularity. It is suitable for the negative electrode of lithium ion capacitors and improves the capacity and magnification performance.
Smart Images

Figure CN119370830A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of novel carbon materials, and in particular to a nano carbon cage and a preparation method and application thereof. Background Art
[0002] As a new type of nanocarbon material, nanocarbon cages have gradually become a new platform for energy storage and conversion, and have received extensive attention from academia and industry in recent years. Nanocarbon cages have a unique hollow structure and exhibit good conductivity and wettability. Due to their special porous structure and high specific surface area, nanocarbon cages have been widely studied in the field of supercapacitor energy storage. At the same time, as catalyst carriers, nanocarbon cages also show good application prospects in the fields of electrochemistry and chemical engineering.
[0003] At present, the preparation methods of nano carbon cages mainly include chemical vapor deposition, arc discharge method, hard template method, plasma polymerization method, laser evaporation graphite method, etc. The generation mechanism of nano carbon cages is generally divided into two types: one is that under high temperature conditions, nano metal particles catalyze carbon materials to form cavities, and gradually grow to form nano carbon cages; the other is that the carbon source is carbonized on the surface of the template to form a stable carbon coating structure, and then the internal template is removed to obtain the nano carbon cage material. For example, the Hu Zheng team of Nanjing University used magnesium oxide as a template and benzene as an organic carbon source to successfully develop a series of nano carbon cage materials with high specific surface area. In addition, CN1810635A first prepares a large amount of amorphous carbon precursors with uniform distribution of iron catalyst particles, then heat treats the precursors to obtain hollow carbon nano cages through solid-state reactions, and finally performs subsequent treatment of the hollow carbon nano cages to remove the catalyst to obtain the final product. CN108455565A physically mixes cyanamide compounds with metal acetates or metal carbonates, and obtains nitrogen-doped graphitized nano carbon cages through high temperature carbonization and pickling. CN110078051A uses sugar as carbon source and potassium chloride as template, ball milling and mixing, high temperature carbonization, and then soaking to remove the potassium chloride template to obtain nano carbon cage material. CN110272035A successfully prepares nano carbon cage with rich pore structure and large specific surface area by roasting metal organic framework precursor with rhombic dodecahedron structure.
[0004] In summary, the existing methods of nano-carbon cages have problems such as relatively complex production process, high raw material cost and low carbon yield, which makes it difficult to achieve large-scale production. In addition, the regularity and uniformity of the structure of the nano-carbon cages prepared by the existing methods need to be improved. Therefore, finding a preparation method with simple process, low cost and controllable structure is of great significance for the large-scale production and application of nano-carbon cages. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of high cost, complex process and low degree of graphitization of carbon cages in the prior art, and to provide a nano carbon cage and a preparation method and application thereof. The preparation method of the nano carbon cage has low raw material cost and simple process, and the prepared carbon cage has a high degree of graphitization and a controllable structure.
[0006] In order to achieve the above object, the present invention provides a method for preparing a nanocarbon cage, the method comprising:
[0007] (1) physically mixing asphalt and a nickel-containing compound, and then roasting to obtain an intermediate product;
[0008] The softening point of the asphalt is 130-300°C; the calcination temperature is 700-1200°C and the calcination time is 60-240 minutes;
[0009] (2) The intermediate product is acid washed.
[0010] The second aspect of the present invention provides a nanocarbon cage obtained by the above preparation method.
[0011] The third aspect of the present invention provides the use of the above-mentioned nanocarbon cage in a lithium ion capacitor.
[0012] The preparation method of the nano carbon cage provided by the present invention uses asphalt and nickel-containing compounds as raw materials, obtains an intermediate product by physical mixing, and during the roasting process, the asphalt is carbonized, the nickel-containing compound is pyrolyzed, and the reduced nickel atoms act as a catalyst and template, so that the carbon is evenly coated on the outside of the nickel atoms. Finally, the metallic nickel in the initial product is removed by pickling, and a thin layer of nano carbon cage material is obtained after drying. Using asphalt and nickel-containing compounds as raw materials, on the one hand, there is no need to use a nano template agent in the preparation process, which greatly reduces the cost of raw materials, and using asphalt as a carbon source is conducive to improving the carbon yield; on the other hand, using asphalt as a raw material is conducive to improving the graphitization degree of the carbon cage and the cage wall of the nano carbon cage is thin, which is conducive to its application as the negative electrode of the lithium ion capacitor, and improves the specific capacity and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is a transmission electron microscope image of the nanocarbon cage prepared in Example 1;
[0014] Figure 2 is the Raman spectrum of the nanocarbon cage prepared in Example 1;
[0015] Figure 3 is the XRD spectrum of the nanocarbon cage prepared in Example 1;
[0016] Figure 4 is the half-cell rate cycle curve of the negative electrode made of nanocarbon cage S1;
[0017] Figure 5 is the half-cell rate cycle curve of the negative electrode made of nanocarbon cage S2;
[0018] Figure 6 This is the half-cell rate cycle curve of the negative electrode made of nanomaterial DS1. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] The first aspect of the present invention provides a method for preparing a nanocarbon cage, the method comprising:
[0021] (1) physically mixing asphalt and a nickel-containing compound, and then roasting to obtain an intermediate product;
[0022] The softening point of the asphalt is 130-300°C; the calcination temperature is 700-1200°C and the calcination time is 60-240 minutes;
[0023] (2) The intermediate product is acid washed.
[0024] In the present invention, asphalt with a softening point of 130-300°C is uniformly mixed and dispersed with a nickel-containing compound at a physical level, and then the nickel in the intermediate product is removed by pickling, so that the prepared nano-carbon cage has a higher degree of graphitization and a thinner cage wall, which is conducive to improving the specific capacity and rate performance. The reason may be that the asphalt with a softening point of 130-300°C has a larger molecular weight, and it is not easy to form a strict multi-layer coating structure during the pyrolysis process, so that the number of carbon layers is small. In the physical mixing process of the present invention, the asphalt and the nickel-containing compound basically do not produce chemical changes, so that the nickel element can be evenly dispersed in the asphalt during physical mixing. When small molecular organic matter is used as a carbon source in the prior art, the coating is usually relatively tight, the number of carbon layers is large, the nickel ions are not easy to pickle, and the carbon yield is low.
[0025] In addition, the preparation method provided by the present invention uses asphalt, a by-product of petrochemical industry, as a raw material, and no nano-template is required in the preparation process, which greatly reduces the cost of raw materials; using asphalt as a carbon source is beneficial to improving the carbon yield.
[0026] In the present invention, the "asphalt" has the conventional definition in the art, and may be petroleum asphalt and / or coal asphalt.
[0027] In some preferred embodiments of the present invention, the asphalt is ultra-high temperature asphalt, and the softening point of the asphalt is 200-280°C. The use of the above-mentioned preferred asphalt raw material is conducive to obtaining nano-carbon cages with a smaller number of carbon layers, which is further conducive to improving capacity and rate performance.
[0028] Preferably, the content of quinoline insoluble matter in the asphalt does not exceed 10 wt %. In the present invention, the content of quinoline insoluble matter is measured by GB / T2293-80 method.
[0029] According to some preferred embodiments of the present invention, the asphalt includes carbon, hydrogen, oxygen, and optionally nitrogen and sulfur. Based on the total amount of the asphalt, the content of the C element is not less than 90wt%, the content of the H element is not more than 10wt%, the content of the O element is not more than 1wt%, the content of the N element is not more than 1wt%, and the content of the sulfur element is not more than 1wt%. It can be understood by those skilled in the art that the asphalt may also contain other impurity elements, such as metal elements.
[0030] Further preferably, based on the total amount of the asphalt, the content of the C element is 92-98wt%, the content of the H element is 1-6wt%, the content of the O element is 0.1-0.5wt%, the content of the N element is 0-0.5wt%, and the content of the sulfur element is 0-1wt%. Using the asphalt with the above preferred composition as a carbon source is beneficial to reducing the specific surface area of the carbon cage micropores and improving the carbon cage yield.
[0031] In the present invention, the composition of asphalt is tested by an element analyzer.
[0032] According to some preferred embodiments of the present invention, the mass ratio of the asphalt to the nickel-containing compound is 1:(1-8), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, etc., which are typical but not limiting mass ratios or ranges therebetween. Preferably, the mass ratio of the asphalt to the nickel-containing compound is 1:(3-6). Under the above preferred conditions, it is beneficial to obtain a carbon cage with a regular structure and a moderate specific surface area, which can be further applied to lithium ion capacitors to obtain better electrochemical performance, and has both excellent capacity and rate performance.
[0033] The present invention has no particular requirements for the specific operation and conditions of the physical mixing in step (1), as long as it is conducive to uniform mixing of the asphalt and the nickel-containing compound, it can be carried out in a conventional manner in the art.
[0034] According to some preferred embodiments of the present invention, the physical mixing method includes: mixing the asphalt, the nickel-containing compound and the optional dispersant under stirring and / or ball milling conditions.
[0035] Further preferably, the physical mixing method includes: premixing the asphalt, the nickel-containing compound and the optional dispersant under stirring, and then ball milling the premixed mixture. The above preferred embodiment helps to evenly disperse the nickel-containing compound in the asphalt, which is beneficial to improve the regularity and uniformity of the obtained nano-carbon cage structure, and further applied to lithium ion capacitors with higher capacity and better rate performance.
[0036] According to the present invention, preferably, the dispersant is selected from methanol and / or ethanol, preferably ethanol.
[0037] Preferably, the ratio of the amount of the dispersant to the total mass of the asphalt and the nickel-containing compound is 2-15:1, preferably 5-10:1.
[0038] According to the present invention, preferably, the premixing temperature is 60-90°C, preferably 70-80°C, and the premixing time is 1-5h, preferably 2-4h.
[0039] Preferably, the premixing further includes solid-liquid separation and drying steps to remove residual dispersant. The solid-liquid separation and drying steps can be performed in a conventional manner in the art, and the present invention is not particularly limited thereto. For example, the solid-liquid separation can be performed by filtering, suction filtration, centrifugation, etc.
[0040] In the present invention, the ball milling can be performed using a planetary ball mill. Preferably, the ball milling conditions include: a ball milling speed of 300-500 rpm, preferably 350-450 rpm, and a time of 5-20 h, preferably 8-12 h.
[0041] The present invention has a wide range of selection for the specific type of the nickel-containing compound. Preferably, the nickel-containing compound is selected from inorganic salts of nickel, preferably at least one of nickel acetate, nickel nitrate, nickel chloride and basic nickel carbonate, more preferably basic nickel carbonate.
[0042] According to the present invention, during the calcination process of step (1), the asphalt is carbonized, the nickel-containing compound is pyrolyzed, and the reduced nickel atoms act as a catalyst and a template, so that the carbon is evenly coated on the outside of the nickel atoms.
[0043] According to some preferred embodiments of the present invention, the calcination conditions include: a heating rate of 1-10°C / min, a calcination temperature of 700-1200°C, preferably 800-1000°C; and a calcination time of 60-240min, preferably 60-120min.
[0044] According to the present invention, preferably, the calcination is performed under an inert atmosphere, and the inert atmosphere is preferably provided by nitrogen.
[0045] According to the present invention, the metallic nickel in the precursor is removed by pickling in step (2) to form a hollow nano-carbon cage. The specific operation and conditions of the pickling can be selected according to actual needs, as long as the above-mentioned effect can be achieved. The inventors of the present invention have found in their research that it is not easy to form a strict multi-layer coating structure during the pyrolysis process using asphalt with a softening point of 130-300°C, so that the number of carbon layers is small, which makes it easier to remove nickel ions by pickling.
[0046] According to some preferred embodiments of the present invention, the pickling in step (2) comprises: contacting the precursor with an acid solution, followed by washing and drying.
[0047] Preferably, H + The molar mass ratio of the acid solution to the molar mass ratio of the intermediate product is (1-4):1, preferably (2-3):1.
[0048] Preferably, the contacting temperature is 60-120°C, preferably 90-105°C; the contacting time is 2-12h, preferably 4-8h.
[0049] Preferably, the acid solution is an aqueous solution of an inorganic acid and / or an organic acid, more preferably hydrochloric acid. The concentration of the acid solution may be 0.5-2 mol / L, preferably 0.8-1.5 mol / L.
[0050] In the present invention, the washing is used to remove the residual acid solution, and various water washing methods that can wash the nanocarbon cage to neutrality in the art can be applied to the present invention. The drying is used to remove water on the nanocarbon cage, and the drying can also be carried out in a conventional manner.
[0051] The second aspect of the present invention provides a nanocarbon cage obtained by the above preparation method.
[0052] According to the present invention, the nano carbon cage prepared by the above preparation method has a hollow cage structure, and the graphitization degree of the cage wall is relatively high, which is characterized by Raman spectroscopy test.
[0053] Preferably, the Raman curve of the nanocarbon cage is D / I G Less than 1, preferably 0.8-0.95.
[0054] In the present invention, the Raman curve is obtained by Raman spectroscopy testing, and the excitation wavelength is 532 nm.
[0055] In the above preferred case, it is beneficial to use the nanocarbon cage as the negative electrode of the lithium ion capacitor, thereby improving the specific capacity and rate performance.
[0056] Preferably, the specific surface area of the nanocarbon cage is 150-600m 2 / g, preferably 300-500m 2 / g.
[0057] In the present invention, the specific surface area of the sample is measured by a Quantachrome AS-6B analyzer, and the specific surface area of the material is obtained by the Brunauer-Emmett-Taller (BET) method.
[0058] According to the present invention, by using asphalt as a carbon source, while increasing the graphitization degree of the carbon cage, the cage wall of the obtained nanocarbon cage is thinner, which is beneficial to the embedding and extraction of lithium ions when applied to the negative electrode of a lithium ion capacitor, thereby facilitating the improvement of specific capacity and rate performance. Preferably, the average number of carbon layers of the cage wall of the nanocarbon cage is 2-5 layers, preferably 2-3 layers. The average number of carbon layers of the nanocarbon cage generally prepared in the prior art is greater than 5.
[0059] Preferably, the average diameter of the nanocarbon cage is 3-10 nm, preferably 6-8 nm.
[0060] In the present invention, the diameter of the nanocarbon cage and the average number of carbon layers of the cage wall are measured by high-resolution transmission electron microscopy. The model of the high-resolution transmission electron microscope (HRTEM) used in the present invention is JEM-2100 (HRTEM) (Japan Electron Co., Ltd.), and the high-resolution transmission electron microscope test conditions are: the acceleration voltage is 200kV. Specifically, the diameters and carbon layers of 10 carbon cages within the field of view are counted, and their average values are calculated respectively to obtain the diameter of the nanocarbon cage and the average number of carbon layers of the cage wall of the nanocarbon cage.
[0061] The third aspect of the present invention provides the use of the above-mentioned nanocarbon cage in a lithium ion capacitor.
[0062] Compared with the negative electrode of lithium-ion batteries, the negative electrode of lithium-ion capacitors does not require a charging and discharging platform. In order to match the performance of the positive electrode, higher requirements are placed on the specific capacity and rate performance. The nanocarbon cage provided by the present invention can be used alone as a negative electrode of a lithium-ion capacitor in a lithium-ion capacitor, or it can be combined with other negative electrode active materials as a composite negative electrode in a lithium-ion capacitor. The present invention has no special restrictions on this. The nanocarbon cage provided by the present invention has a high degree of graphitization and a thinner cage wall. It has a high specific capacity and excellent rate performance when applied to lithium-ion capacitors.
[0063] The present invention will be described in detail below through examples.
[0064] In the following examples, unless otherwise specified, the raw materials used were commercially available.
[0065] The model of the high-resolution transmission electron microscope (HRTEM) used in the present invention is JEM-2100 (HRTEM) (Japan Electron Co., Ltd.), and the test conditions of the high-resolution transmission electron microscope are: the acceleration voltage is 200 kV.
[0066] In the present invention, the specific surface area of the sample is measured by a Quantachrome AS-6B analyzer, and the specific surface area of the material is obtained by the Brunauer-Emmett-Taller (BET) method.
[0067] The Raman curve is measured by Raman spectroscopy, and specific test conditions include: the excitation wavelength is 532nm.
[0068] The X-ray diffraction (XRD) test conditions in the present invention are: Cu target, Kα ray (wavelength λ=0.154nm), tube voltage of 40kV, tube current of 200mA, and scanning speed of 5° / min.
[0069] In the present invention, the negative electrode performance of the thin-layer nano-carbon cage material is obtained by testing at different current densities using the Wuhan Blue Electricity Testing System.
[0070] Example 1
[0071] The ultra-high temperature petroleum asphalt powder used in this embodiment comprises: a carbon content of 93.3%, an oxygen content of 0.21%, a sulfur content of 0.77%, a hydrogen content of 5.51%, and the rest are impurity elements; the content of quinoline insolubles is ≤10wt%, and the softening point is 280°C.
[0072] Mix 1g of ultra-high temperature asphalt powder, 3g of basic nickel carbonate and 50mL of anhydrous ethanol, heat and reflux at 80°C for 4h, filter and place in an oven to dry. Transfer the dried mixture to a ball mill and mill it for 12h at 400 rpm in a planetary ball mill. Pour the ball-milled powder into a ceramic crucible and place it in a tubular calcining furnace. Under the protection of nitrogen, heat to 800°C at a heating rate of 5°C / min, calcine at a constant temperature for 2h, and finally cool naturally to room temperature to obtain a black intermediate product.
[0073] Then, the intermediate product was added to 50 mL of deionized water, stirred evenly, and then a hydrochloric acid solution (concentration of 1 mol / L) with a molar mass of 2 times that of the intermediate product was added. Then, the temperature was raised to 105°C and heated and stirred for 8 hours. After cooling to room temperature, the mixture was filtered and washed with water until neutral. The mixture was placed in an oven and dried overnight to obtain a thin layer of nanocarbon cage material S1, and the physicochemical properties are shown in Table 1.
[0074] Figure 1 TEM image of nanocarbon cage S1. Figure 1It can be seen that the nanocarbon cage has a hollow cage structure; the Raman curve and XRD curve are as follows Figure 2 and Figure 3 As shown, it can be shown that the material has a high degree of graphitization.
[0075] Example 2
[0076] The ultra-high temperature petroleum asphalt powder used in this embodiment comprises: a carbon content of 93.3%, an oxygen content of 0.21%, a sulfur content of 0.77%, a hydrogen content of 5.51%, and the rest are impurity elements; the content of quinoline insolubles is ≤10wt%, and the softening point is 280°C.
[0077] Mix 1g of ultra-high temperature asphalt powder, 4g of basic nickel carbonate and 50mL of anhydrous ethanol, heat and reflux at 80°C for 4h, filter and place in an oven to dry. Transfer the dried mixture to a ball mill and mill it for 8h at 450 rpm in a planetary ball mill. Pour the ball-milled powder into a ceramic crucible and place it in a tubular calcining furnace. Under the protection of nitrogen, heat to 900°C at a heating rate of 5°C / min, calcine at a constant temperature for 2h, and finally cool naturally to room temperature to obtain a black intermediate product.
[0078] Then, the intermediate product was added to 50 mL of deionized water, stirred evenly, and then a hydrochloric acid solution (concentration of 1 mol / L) with a molar mass of 2 times that of the intermediate product was added. Then, the temperature was raised to 105°C and heated and stirred for 8 hours. After cooling to room temperature, the mixture was filtered and washed with water until neutral. The mixture was placed in an oven and dried overnight to obtain a thin layer of nanocarbon cage material S2, the physical and chemical properties of which are shown in Table 1.
[0079] Example 3
[0080] The ultra-high temperature petroleum asphalt powder used in this embodiment comprises: a carbon content of 93.3%, an oxygen content of 0.21%, a sulfur content of 0.77%, a hydrogen content of 5.51%, and the rest are impurity elements, a quinoline insoluble content of ≤10wt%, and a softening point of 280°C.
[0081] Mix 1g of ultra-high temperature asphalt powder, 6g of basic nickel carbonate and 50mL of anhydrous ethanol, heat under reflux and stir at 80°C for 4h, filter and place in an oven to dry. Transfer the dried mixture to a ball mill and mill it for 8h at 400 rpm in a planetary ball mill. Pour the ball-milled powder into a ceramic crucible and place it in a tubular calcining furnace. Under the protection of nitrogen, heat to 1000°C at a heating rate of 5°C / min, calcine at a constant temperature for 2h, and finally cool naturally to room temperature to obtain a black intermediate product.
[0082] Then, the intermediate product was added to 50 mL of deionized water, stirred evenly, and then a hydrochloric acid solution (concentration of 1 mol / L) with a molar mass of 2 times that of the intermediate product was added. Then, the temperature was raised to 105°C and heated and stirred for 8 hours. After cooling to room temperature, the mixture was filtered and washed with water until neutral. The mixture was placed in an oven and dried overnight to obtain a thin layer of nanocarbon cage material S3, the physical and chemical properties of which are shown in Table 1.
[0083] Example 4
[0084] The method of Example 1 is followed, except that the calcination conditions include: under the protection of nitrogen, heating to 1100° C. at a heating rate of 5° C. / min, and calcining at a constant temperature for 2 hours. The prepared nanocarbon cage material is denoted as S4, and the physicochemical properties are shown in Table 1.
[0085] Example 5
[0086] The composition of the asphalt powder used in this embodiment includes: a carbon content of 92.27%, an oxygen content of 0.24%, a sulfur content of 0.32%, a hydrogen content of 7.17%, and the rest are impurity elements; the content of quinoline insolubles is ≤5wt%, and the softening point is 150°C.
[0087] The method of Example 1 is followed, except that the above-mentioned asphalt powder is used to replace the ultra-high temperature asphalt powder in Example 1. The prepared carbon cage material is denoted as S5, and the physicochemical properties are shown in Table 1.
[0088] Example 6
[0089] The ultra-high temperature petroleum asphalt powder used in this embodiment comprises: a carbon content of 93.3%, an oxygen content of 0.21%, a sulfur content of 0.77%, a hydrogen content of 5.51%, and the rest are impurity elements; the content of quinoline insolubles is ≤10wt%, and the softening point is 280°C.
[0090] 1 g of ultra-high temperature asphalt powder and 3 g of basic nickel carbonate were ground and mixed, then placed in a tubular calcining furnace. Under the protection of nitrogen, the temperature was increased to 800 °C at a heating rate of 5 °C / min, and the mixture was calcined at a constant temperature for 2 h. Finally, the mixture was naturally cooled to room temperature to obtain a black intermediate product.
[0091] Then, the intermediate product was added to 50 mL of deionized water, stirred evenly, and then a hydrochloric acid solution (concentration of 1 mol / L) with a molar mass of 2 times that of the intermediate product was added. Then, the temperature was raised to 105°C and heated and stirred for 8 hours. After cooling to room temperature, the mixture was filtered and washed with water until neutral. The mixture was placed in an oven and dried overnight to obtain a thin layer of nanocarbon cage material S6, the physical and chemical properties of which are shown in Table 1.
[0092] Comparative Example 1
[0093] The ultra-high temperature asphalt powder used in this comparative example is the same as that in Example 1.
[0094] 1g of ultra-high temperature asphalt powder was placed in a tubular calcining furnace. Under the protection of nitrogen, the temperature was raised to 800°C at a heating rate of 5°C / min, and the mixture was calcined at a constant temperature for 2h. Finally, the mixture was naturally cooled to room temperature to obtain the final product, which was recorded as DS1. The physical and chemical properties are shown in Table 1. TEM characterization showed that the material did not have a cage structure.
[0095] Comparative Example 2
[0096] The asphalt used in this comparative example is sulfonated asphalt powder, and its composition includes: carbon content of 40.24wt%, oxygen content of 17.87wt%, sulfur content of 1.4wt%, hydrogen content of 3.82wt%, and the rest are impurity elements, the content of quinoline insoluble matter is ≤20wt%, and the softening point is 120°C.
[0097] Mix 1g of sulfonated asphalt powder, 3g of basic nickel carbonate and 50mL of anhydrous ethanol, heat and stir at 80℃ for 4h, filter and place in an oven to dry. Then pour into a ceramic crucible and place in a tubular calcining furnace. Under the protection of nitrogen, heat to 800℃ at a heating rate of 5℃ / min, calcine at a constant temperature for 2h, and finally cool naturally to room temperature to obtain a black intermediate product.
[0098] Then, the intermediate product was added to 50 mL of deionized water, stirred evenly, and then a hydrochloric acid solution (concentration of 1 mol / L) with a molar mass of 2 times that of the intermediate product was added. Then, the temperature was raised to 105 ° C and heated and stirred for 8 hours. After cooling to room temperature, the mixture was filtered and washed with water until neutral. It was placed in an oven and dried overnight to finally obtain the carbon material DS2, and the physicochemical properties are shown in Table 1. TEM characterization showed that the material did not have a cage structure.
[0099] Table 1
[0100] serial number <![CDATA[Specific surface area m 2 / g]]> Average number of carbon layers on cage wall Average diameter nm <![CDATA[Raman I D / I G > S1 357.4 3 6 0.83 S2 508.6 2 8 0.93 S3 431.7 2 8 0.95 S4 279.3 2 7 0.98 S5 340.5 4 8 0.98 S6 287.6 3 6 0.85 DS1 2.36 - - 0.99 DS2 342.4 - - 0.99
[0101] Application Examples
[0102] The carbon material, acetylene black and polyvinylidene fluoride prepared in the above examples and comparative examples were mixed in a mass percentage of 8:1:1, 400 mg N-methylpyrrolidone was added, and the mixture was fully mixed using a homogenizer. The slurry was then scraped onto the copper foil current collector and dried at 80°C in a vacuum oven to obtain the negative electrode of the lithium ion capacitor. A 2032 type button cell was made in a glove box using a metal lithium sheet as the counter electrode. The diaphragm used was an ordinary celgard2400 diaphragm, and the electrolyte used was LiPF 6 / ethylene carbonate (EC): diethyl carbonate (DEC) (EC:DEC = 1:1, 5wt% fluoroethylene carbonate FEC). The prepared half-cell was left to stand for 3 hours, and then its performance was tested by a blue electric test system. The test conditions were: at room temperature, the charge and discharge tests were carried out at current densities of 0.1A / g, 1A / g and 10A / g, respectively, and the test voltage range was 0-3V. The results are shown in Table 2.
[0103] Among them, the rate cycle curve of S1 is as follows Figure 4 As shown, the curve of the rate cycle of S2 is as follows Figure 5 As shown, the curve of DS1 rate cycle is as follows Figure 6 shown.
[0104] Table 2
[0105]
[0106] Combining the results of Table 1 and Table 2, it can be seen that the nanocarbon cage prepared by the preparation method provided by the present invention has a high specific surface area, a high degree of graphitization, a small average number of cage walls, and a thin cage wall. The nanocarbon cage is used as a negative electrode material. S1, S2, and S3 prepared under preferred conditions all show a high specific capacity and excellent rate performance. Comparative Example 2 uses sulfonated asphalt with a low softening point as a raw material to prepare a carbon material. Because of the high heteroatom content, a specific capacity comparable to that of Example 1 can be obtained at a current density of 0.1A / g, but the capacity is insufficient at a high current density.
[0107] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a nanocarbon cage, characterized in that: The method comprises: (1) physically mixing asphalt and a nickel-containing compound, and then roasting to obtain an intermediate product; The softening point of the asphalt is 130-300°C; the calcination temperature is 700-1200°C and the calcination time is 60-240 minutes; (2) The intermediate product is acid washed.
2. The preparation method according to claim 1, wherein The asphalt is petroleum asphalt and / or coal asphalt; Preferably, the softening point of the asphalt is 200-280°C; Preferably, the content of quinoline insoluble matter in the asphalt does not exceed 10wt%; Preferably, the asphalt includes carbon, hydrogen, oxygen, and optionally nitrogen and optionally sulfur elements. Based on the total amount of the asphalt, the content of the C element is not less than 90wt%, the content of the H element is not more than 10wt%, the content of the O element is not more than 1wt%, the content of the N element is not more than 1wt%, and the content of the sulfur element is not more than 1wt%; Preferably, based on the total amount of the asphalt, the content of element C is 92-98wt%, the content of element H is 1-6wt%, the content of element O is 0.1-0.5wt%, the content of element N is 0-0.5wt%, and the content of element sulfur is 0-1wt%.
3. The preparation method according to claim 1 or 2, wherein The physical mixing method includes: mixing the asphalt, the nickel-containing compound and the optional dispersant under stirring and / or ball milling conditions; Preferably, the mass ratio of the asphalt to the nickel-containing compound is 1:(1-8), preferably 1:(3-6).
4. The preparation method according to claim 3, wherein The physical mixing method includes: premixing the asphalt, the nickel-containing compound and the optional dispersant under stirring conditions, and then ball milling the premixed mixture; Preferably, the dispersant is selected from methanol and / or ethanol, preferably ethanol; Preferably, the ratio of the amount of the dispersant to the total mass of the asphalt and the nickel-containing compound is 2-15:1, preferably 5-10:1; Preferably, the premixing temperature is 60-90°C and the time is 1-5h; Preferably, the ball milling conditions include: a ball milling speed of 300-500 rpm, preferably 350-450 rpm, and a time of 8-20 h, preferably 8-12 h.
5. The preparation method according to any one of claims 1 to 4, wherein: The nickel-containing compound is selected from inorganic salts of nickel, preferably at least one of nickel acetate, nickel nitrate, nickel chloride and basic nickel carbonate, more preferably basic nickel carbonate.
6. The preparation method according to any one of claims 1 to 5, wherein: The calcination conditions include: a heating rate of 1-10°C / min, a calcination temperature of 800-1000°C, and a time of 60-120min; Preferably, the calcination is carried out under an inert atmosphere, which is preferably provided by nitrogen.
7. The preparation method according to any one of claims 1 to 6, wherein: The acid washing in step (2) comprises: contacting the intermediate product with an acid solution, and then washing with water and drying; Preferably, H + The molar ratio of the acid solution to the intermediate product is (1-4): 1; Preferably, the contacting temperature is 60-120°C, preferably 90-105°C; the contacting time is 2-12h, preferably 4-8h; Preferably, the acid solution is an aqueous solution of an inorganic acid and / or an organic acid, preferably hydrochloric acid.
8. The nanocarbon cage obtained by the preparation method according to any one of claims 1 to 7.
9. The nanocarbon cage according to claim 8, wherein: The specific surface area of the nanocarbon cage is 150-600m 2 / g; Preferably, the average number of carbon layers of the cage wall of the nanocarbon cage is 2-5 layers, preferably 2-3 layers; Preferably, the average diameter of the nanocarbon cage is 3-10 nm, preferably 6-8 nm; Preferably, the Raman curve of the nanocarbon cage is D / I G Less than 1.
10. Use of the nanocarbon cage according to claim 8 or 9 in a lithium ion capacitor.
Citation Information
Patent Citations
Preparation method of nitrogen-doped graphitized carbon nanocage
CN108455565A
Preparation method of carbon nano cage material
CN110078051A
Method for preparing carbon nano-cage by catalyzing organic ligand by metal ion, prepared carbon nano-cage and application of carbon nano-cage
CN110272035A
Method for preparing anode material of lithium ion battery with hollow opening onion-like carbon structure
CN109319757A
Nanometer cage-shaped coal pitch derived carbon material as well as preparation method and application thereof
CN112960664A